2007
DOI: 10.1016/j.respol.2007.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Profit distribution and compensation structures in publicly and privately funded hybrid venture capital funds

Abstract: Policy makers have become increasingly concerned at the lack of risk capital available to new and early stage entrepreneurial ventures. As a public response to a perceived market failure, several governments have set up programs to channel equity finance to capital constrained but high potential, young enterprises. Critically, government support is often directed through the agency of private venture capital funds. We examine the profit distribution and compensation structures used in these hybrid public/priva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 36 publications
(70 reference statements)
0
52
0
2
Order By: Relevance
“…Also, there are researches that it is not sure if government VC crowd-in or -out other VCs (Leleux and Surlemont, 2003), that they do not crowd-out at least (Cumming, 2014), and that they only can solve relatively modest market failures (Jääskeläinen et al, 2007).…”
Section: Do Government Venture Capitals Contribute To Their Portfolios?mentioning
confidence: 99%
“…Also, there are researches that it is not sure if government VC crowd-in or -out other VCs (Leleux and Surlemont, 2003), that they do not crowd-out at least (Cumming, 2014), and that they only can solve relatively modest market failures (Jääskeläinen et al, 2007).…”
Section: Do Government Venture Capitals Contribute To Their Portfolios?mentioning
confidence: 99%
“…The review of Australian Pre-Seed Fund established in 2002, previously an Innovation Investment Fund (Australia) which had been operating since 1997 (Cumming 2007) has found that its investments are no more likely to be made in innovative and high technology companies than the average for a fund of this size, in spite of the fact that the rules of the fund management require investments into firms that are capitalizing upon and exploiting the scientific discoveries that have been made in universities and public laboratories or be connected to a grant (and that such firms be controlled by a university, public sector research agency or qualifying researcher or that they use intellectual property that is at least 50% owned by a university, public sector research agency or qualifying researcher). That a fund targeting what should be high technology firms should in practice give no more support to high technology firms than the typical fund may suggest problems with the management and operation of the fund (Jääskeläinen et al 2007). …”
Section: The Innovation Impactmentioning
confidence: 99%
“…A study carried out by Jääskeläinen et al (2007) examines, using simulation, the characteristics of hybrid funds (profit distribution and compensation structures) and attempt to define and identify the conditions under which early stage CV hybrid funds may operate profitably. The research has important conclusions for the operation of venture capital funds supported by government.…”
Section: Other System Level Concernsmentioning
confidence: 99%
“…Specifically, we investigate the extent to which private and governmental VCs differ in their impact on firms' innovation output. In one respect, private VCs, as a result of their governance structure and profit-oriented behavior (Jääskeläinen et al, 2007), may possess better skills and incentives to spur innovation than governmental VCs. At the same time, private VCs may suffer from short-termism (Gompers, 1996), which could hamper R&D spending and innovation (Lerner, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Second, private VCs may have better skills than governmental VCs in selecting promising portfolio companies and in coaching and monitoring these companies (Leleux and Surlemont, 2003;Luukkonen and Maunula, 2007b;Luukkonen et al, 2011), which, again, may lead to a greater innovative output of these companies. Third, in general, private VCs have more performance-sensitive contracts than governmental VCs (Jääskeläinen et al, 2007). Therefore, private VCs posses increased incentives to provide their portfolio firms with the financial and non-financial resources they need to pursue the development of innovations.…”
mentioning
confidence: 99%